2011
DOI: 10.1080/01635581.2011.606392
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hypoproteinemia in Cancer Patients Following Extensive Abdominal Surgery Despite Parenteral Nutritional Support

Abstract: Determination of the predictors of hypoproteinemia among cancer patients following extensive surgery may enhance their nutritional management and clinical outcome. This study evaluated the predictive factors of postoperative hypoproteinemia among cancer patients following extensive abdominal surgery. An age- and gender-matched case-control study (n = 115) was conducted among cancer patients undergoing extensive (cases; n = 81) and moderate (controls; n = 34) abdominal surgery. Case patients received total pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…Fasting, reduced protein-calorie intake, and increased catabolic activity triggered by the stress of surgery are reflected in the decrease in analytical parameters such as urea and serum proteins. This decrease seems to be directly related to the degree of surgical stress to which the patient is subjected [26,27]. In our study, we only observed differences in glucose, urea, and zinc postoperative laboratory parameters between the PPN and FT groups in the short-term follow-up.…”
Section: Discussioncontrasting
confidence: 42%
“…Fasting, reduced protein-calorie intake, and increased catabolic activity triggered by the stress of surgery are reflected in the decrease in analytical parameters such as urea and serum proteins. This decrease seems to be directly related to the degree of surgical stress to which the patient is subjected [26,27]. In our study, we only observed differences in glucose, urea, and zinc postoperative laboratory parameters between the PPN and FT groups in the short-term follow-up.…”
Section: Discussioncontrasting
confidence: 42%
“…It leads to increased postoperative morbidity, being the main cause of mortality after intestinal resections. Identification of predisposing factors is paramount in the prevention of anastomotic leakage [ 6 ] We only found studies analyzing the connection between albumin and surgical complications such as anastomotic leakage in colorectal cancer surgery [ 7 , 8 ] and only preoperatively, while few other studies debated the problem of postoperative low total serum protein values in abdominal cancer surgery [ 9 ] and an unfavorable outcome.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Eligibility for study participation was assessed upon hospital admission and one day prior to surgery (Critselis et al 2011). Eligible participants were aged between 18 and 85 years old with a primary or recurrent carcinoma of the lower gastrointestinal and/or urogenital tract.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%